Galerie 't venster : verslag 1979. - Galerie 't Venster, Rotterdam (Rotterdam : Rotterdamse Kunststichting, 1980)
van 't Slot, John ; Wiersma, Pieter ; Seidenstücker, Friedrich ; Sandoz, Claude ; Trotta, Antonio ; Weiss, David ; Buthe, Michael ; Kirili, Alain ; Lutgerink, Ton ; van Oord, Johan ; Paladino, Mimmo ; etc.
Nederlands & Engels
boek